Analysis of Dengue Hemorrhagic Fever in Adult Patients in Panti Rahayu Yakkum Purwodadi Hospital - Milga Mahargyaning Vianda Widodo; Endang Setyowati; Ulviani Yulia Husna (Advances in Healthcare Research, 2026)
Purpose: This study aimed to analyze the treatment of dengue hemorrhagic fever in adult inpatients at Panti Rahayu Yakkum Purwodadi Hospital and to evaluate the appropriateness of therapy based on the 2020 Indonesian Ministry of Health guideline. Research Method: This research used a non-experimental observational design with a retrospective descriptive-analytic approach. Data were collected from the medical records of 95 adult inpatients diagnosed with dengue hemorrhagic fever during January-September 2025 using purposive sampling. The variables included patient characteristics, supportive therapy, concomitant drugs, and therapeutic appropriateness. Data were analyzed descriptively and evaluatively. Results and Discussion: The most frequently used therapies were Ringer Lactate infusion (96.84%), paracetamol 500 mg (50.53%), and intravenous paracetamol (45.26%). Evaluation showed appropriate indication in 70.5% of cases, appropriate drug in 51.6%, appropriate patient in 93.7%, and appropriate dose in 95.8%. The findings indicate that dengue treatment was largely dominated by supportive therapy, although some inappropriate drug use was still identified. Implications: The findings underscore the importance of adherence to clinical guidelines for improving therapeutic safety and effectiveness. Further studies are recommended to examine the relationship between therapeutic appropriateness, clinical outcomes, complications, and length of hospitalization.